2013
DOI: 10.1002/gcc.22128
|View full text |Cite
|
Sign up to set email alerts
|

SMARCB1 expression in epithelioid sarcoma is regulated by miR‐206, miR‐381, and miR‐671‐5p on Both mRNA and protein levels

Abstract: Proximal type epithelioid sarcoma shares similarities with malignant rhabdoid tumor, including the lack of nuclear immunoreactivity of SMARCB1. Biallelic mutation of SMARCB1 has been convincingly established as the cause of loss of protein expression in rhabdoid tumor, but the cause in epithelioid sarcoma remains unknown. In our previous work, we demonstrated that DNA hypermethylation and post-translational modification mechanisms were not involved. In this current work, we explored the hypothesis that miRNAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 49 publications
1
46
0
1
Order By: Relevance
“…In this regard, ES is unique because it seems that in this tumor, both genetic and epigenetic regulation may play a role. In our recently published works, we on the one hand proved that loss of SMARCB1 expression in ES is caused neither by DNA hypermethylation nor by post‐translational modifications (Papp et al, ), and on the other hand, we also proved that the SMARCB1 gene is regulated by oncomiR‐206, oncomiR‐381 and oncomiR‐671‐5p (functionally active miRNAs) at both the mRNA and protein levels (Papp et al, ). We also found that miR‐765 was significantly overexpressed in ES, but miR‐765 had no functional activity to silence SMARCB1 mRNA (Papp et al, ).…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…In this regard, ES is unique because it seems that in this tumor, both genetic and epigenetic regulation may play a role. In our recently published works, we on the one hand proved that loss of SMARCB1 expression in ES is caused neither by DNA hypermethylation nor by post‐translational modifications (Papp et al, ), and on the other hand, we also proved that the SMARCB1 gene is regulated by oncomiR‐206, oncomiR‐381 and oncomiR‐671‐5p (functionally active miRNAs) at both the mRNA and protein levels (Papp et al, ). We also found that miR‐765 was significantly overexpressed in ES, but miR‐765 had no functional activity to silence SMARCB1 mRNA (Papp et al, ).…”
Section: Introductionmentioning
confidence: 67%
“…In our recently published works, we on the one hand proved that loss of SMARCB1 expression in ES is caused neither by DNA hypermethylation nor by post‐translational modifications (Papp et al, ), and on the other hand, we also proved that the SMARCB1 gene is regulated by oncomiR‐206, oncomiR‐381 and oncomiR‐671‐5p (functionally active miRNAs) at both the mRNA and protein levels (Papp et al, ). We also found that miR‐765 was significantly overexpressed in ES, but miR‐765 had no functional activity to silence SMARCB1 mRNA (Papp et al, ). In the present study, we wanted to examine whether overexpression of functionally active miRNAs in silencing SMARCB1 mRNA is characteristic or not for the other types of SMARCB1 immunonegative soft tissue sarcomas and whether overexpression of miR‐765 is specific for ES or not.…”
Section: Introductionmentioning
confidence: 67%
“…It is interesting to note, with respect to our patient's history of HIV infection, that the INI1 gene produces a host factor for the HIV virus and its integration. Studies suggest these silencing events may occur through action of OncomiRs, or microRNAs that interfere with the coding of this protein 7. OncomiRs have been implicated in virus-induced tumourigenesis by Epstein-Barr virus.…”
Section: Discussionmentioning
confidence: 99%
“…Papp et al hypothesized that miRNAs regulate SMARCB1 expression and analyzed eight candidate miRNAs selected from in silico analysis. RT-PCR using tumor samples identified the overexpression of miR-206, -381, -671-5p, and -765 in epithelioid sarcomas [69]. Examination of the effect of miRNA transfections revealed that three of the overexpressed miRNAs (miR-206, miR-381, and miR- 671-5p) could silence SMARCB1 mRNA expression in cell cultures.…”
Section: Aberrant Mirna Expression In Soft Tissue Sarcomas (Table 1)mentioning
confidence: 99%
“…Examination of the effect of miRNA transfections revealed that three of the overexpressed miRNAs (miR-206, miR-381, and miR- 671-5p) could silence SMARCB1 mRNA expression in cell cultures. They concluded that the epigenetic mechanism of gene silencing by miRNAs caused the loss of SMARCB1 expression in epithelioid sarcoma [69]. …”
Section: Aberrant Mirna Expression In Soft Tissue Sarcomas (Table 1)mentioning
confidence: 99%